Pencirian resonan plasmon permukaan dan penggunaan saput tipis emas sebagai lapisan aktif sensor optik - Mokhtar, Rosmiza; Abd. Moksin, Mohd Maarof; Mat Yunus, Wan Mahmood (Universiti Putra Malaysia Press, 2000)
The characterizations of a surface plasmon resonance (SPR) of gold thin film at various film thickness are discussed. The measurements have been carried out for film thickness from 50.98 nm to 92.38 nm and the suitable thickness of gold film for SPR optical sensor was found as ≈ 50 nm which produces minimum reflectivity and sharp resonance. The potential application of the SPR as an optical sensor has been explored in measuring small percentage of ethanol in distilled water. The calibration curve was linear with the sensitivity recorded as 9 3 10.2/ (%vol. ethanol) for the concentration of ethanol in water 15%.